A Critical Friendship : Donald Justice and Richard Stern, 1946-1961 - Stern, Richard, 1928-2013; Justice, Donald, 1925-2004; Murphy, Elizabeth, 1983- (Book collections on Project MUSE., 2013)
"A selection of letters from the first fifteen years of a sixty-year friendship between American poet Donald Justice and American novelist Richard Stern"--